Estilos de aprendizaje en estudiantes del primer y quinto grado de secundaria - Duran Huayllani, Daniel Antonio (2025)
The objective of the research was to identify the predominant learning styles in first and fifth grade high school students of the State Educational Institution in Acobamba, Huancavelica. The method used was a descriptive approach to describe and identify the variable, with a basic and pure purpose, collecting information from reality to enrich the scientific theoretical knowledge. The research was of the primary type, using first-hand data. The design was non-experimental, cross-sectional and descriptive, with a sample of 100 students. A survey was conducted through a Honey-Alonso questionnaire (CHAEA), with reliabilities of 0.6272 for the active style, 0.7275 for the reflective style, 0.6584 for the theoretical style and 0.5854 for the pragmatic style. The results in the pretest, the theoretical learning style predominated with 49%, followed by the pragmatic (23%), active (16%) and reflective (12%) styles. The theoretical style was the most used in both first and fifth grade of secondary school. In terms of gender, both genders predominantly used the theoretical style. According to age, students aged 11 years showed a predominance of the pragmatic and theoretical style, while those aged 12 to 17 years had a predominance of the theoretical style, and those aged 18 years presented active and pragmatic styles. Upon entering the institution, students showed theoretical and pragmatic styles, maintaining these styles upon graduation.